Pengaruh Merokok terhadap Penurunan Arus Puncak Ekspirasi pada Perokok Aktif dan Pasif di Kelurahan Barabai Barat - Meiliyani, Aisya Nur, Umi Budi Rahayu, SSt. Ft. SPd. M. Kes (2017)
Smoking is a cylinder of paper a length between 70 and 120 mm with a diameter of about 10 mm containing tobacco leaves that have been shredded. Smoking can cause diseases such as coronary heart disease, stroke and cancer. And cigarette smoke contains thousands of toxic chemicals may cause irritation to the eyes, nose, throat, stimulates the recurrence of asthma, lung cancer and other respiratory disorders. Habit will damage the immune system of the lungs, vibrating bristles that exists and functions normally attack foreign substances that enter and throw it out to be disturbed in the process of expiration especially on peak expiratory flow. The aim of this research is to determine the effect of smoking on the long decline in peak expiratory flow in active and passive smokers. This research is an analytical observational survey using cross-sectional design. This research requires 80 subjects. Data were obtained through interviews and direct observation by researchers. The results of this study showed that the difference in peak expiratory flow values in active smokers and passive with p value 0.001 <0.05 using the Mann Whitney test. There is a long effect of smoking on peak expiratory flow decrease in active smokers and passive.